CESifo World Economic Survey August 2016 - Johanna Garnitz; Gernot Nerb; Dorine Boumans; Julian Dieler; Niko Jaakkola (CESifo World Economic Survey, 2016)
World Economic Climate: World Economic Climate suffers setback - Economic Expectations: Economic expectations downwardly revised - Inflation: Inflation to remain low in most countries - Currencies: US dollar expected to rise further - Interest Rates: Interest rates expected to remain low - Special Topic: Economic decision-makers' expectations of climate policy
Keywords: 330; World Economiy Survey; World Economic Climate; Economic Expectations; Inflation; Interest rates; Currencies